Environmental Consequences of the Urban Sprawl in the Suburban Zone of Nitra: An Analysis Based on Landcover Data - Hardi, Tamás; Repaská, Gabriela; Veselovský, Ján; Vilinová, Katarína (Geographica Pannonica, 2020)
One of the most important territorial processes in the highly urbanised continent of Europe is suburbanisation, urban sprawl which occurs in a gradual manner over long periods and is not perceived as dramatic. Nevertheless the built-up urban areas and the urban lifestyle occupy step by step the periurban territories. Urban sprawl affects the essential environmental, economic and social functions of the impacted settlements. In the last decades these processes reached the less urbanised Central European region, leading to very fast and less planned changes in its settlement system. The research deals with these processes in the Central European non-metropolitan areas, around regional centres, and with their environmental impacts. The aim of this paper is, based on theoretical and empirical knowledge, to point out to spatial patterns of urban sprawl and suburbanisation in functional urban areas (FUA). This paper examines the urban sprawl and its impacts in Slovakia in the case of Nitra Functional Urban Area, in the agglomeration of an economically growing regional centre. The research is based on standard geographical methods including field research. Desktop and field empirical researches were conducted, with different methods such us GIS analysis of land use change. The analysis shows then to what extent cities and urban areas grow, from which one can conclude to how landscape surrounding the urban residential areas has changed, how the proportion of non-permeable surfaces increased, basically influencing the runoff of precipitation. The data demonstrate, moreover, how artificial patches and barriers fragment landscape more and more, endangering thereby biodiversity and decreasing green surfaces. The examination covers the 2000-2018 period, using the CORINE CLC 2000, 2006, 2012 and 2018 databases. Thereby the authors are able to examine changes in a longer period of almost two decades, and three internal periods. All this is compared to the demographic changes of the urban area of Nitra as well, in order to see to what extent the change in the number of population contributes to the transformation of land cover and thereby to environmental impacts. The characteristic features of Nitra and its hinterland within this are analysed, then the Nitra FUA and within that the suburban zone is examined in detail. Nitra and its area feature high enlargement dynamics looking at the whole of the period, compared to other FUAs. It is typical almost everywhere that the enlargement of areas surrounding cities is more intensive than the growth of the city itself, which demonstrates general suburbanisation.
Keywords: Suburbanization urban sprawl land cover change environmental impact Slovakia Nitra